THE ROLE OF DIGITAL TECHNOLOGIES IN SHAPING INNOVATION AND BUSINESS MODELS IN UZBEKISTAN - Khairulla Fayzullaevich Sattarov (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
In today’s competitive and globalized environment, innovation is an important factor for the sustainable functioning of organizations, enabling enterprises to reduce environmental impacts and address social problems. In the context of accelerating innovation processes, managers are forced to reconsider the value creation chain, where digital transformation emerges as a continuous process of adapting to the changing needs of society. This research question aims to determine how digital technologies such as artificial intelligence, big data, cloud computing technologies, industrial and service robots, and the Internet of Things (IoT) affect innovation-based revenues of enterprises in Uzbekistan. The study evaluates the individual impact of each digital technology on innovation revenues using neural network analysis and examines their influence on types of social innovation within organizations. The results demonstrate the central role of digital technologies in enhancing innovation and competitiveness and have important practical implications for managers and policymakers. These findings emphasize the need for enterprises in Uzbekistan to strategically implement digital technologies to ensure long-term competitiveness, especially in the context of the rapid development of the digital economy in the country.